PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Gulo, Dominika Dewi Strisna; Laoli, Bezisokhi; Laoli, Eka Septianti; Lase, Asali (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
Conventional learning methods that are still applied by teachers experience several obstacles, including many students who cannot understand the material being taught. Students tend to be passive and do not respond to the material presented, this affects the learning outcomes of students who do not meet the minimum completeness criteria. The purpose of this study was to determine the development of interactive video learning media in improving student learning outcomes. The method used in this study is the research and development method or Research and Development (R & D). The model used in this study is the development of the 4-D (Four D) model. The results of this study indicate that the assessment of the feasibility of interactive video learning media by material experts is very valid with a percentage of 93%, and the results of the feasibility of interactive video language based on learning aspects have been valid with a percentage of 90%. The results of the feasibility of interactive video media based on material editing aspects have been valid with a percentage of 83%. The response of students to the interactive learning video individual test was 80.35% (practical) while in the field test it reached 93.68% (very practical) while student learning outcomes based on validation reached 85.77%. The effectiveness of interactive learning videos is marked by student learning completion with an average of 90%. From this, it can be concluded that interactive learning videos can improve student learning outcomes.